F.I. Shmit – the Chairman of the Free Faculty of Arts - R.I. Filippenko (Ученые записки Казанского университета: Серия Гуманитарные науки)
An extremely poorly known stage in the cultural life of Kharkov during the Civil War period was considered. The Free Faculty of Arts, which was headed by F.I. Shmit, an outstanding historian and art expert, was founded in the autumn of 1919. The brilliant scientists and teachers of Kharkov became the organizers and lecturers of the faculty. A number of examples were provided to prove that Kharkov of that period was very interested in studying cultural and art criticism. At the same time, the historical situation influenced both students and educational process. The schedule of classes and lecture topics were published in the local press one week prior. No diplomas of previous education were required for being admitted to the Free Faculty of Arts, and students who successfully finished the course were not given any diplomas either. Based on the results of the study, it was concluded that the Free Faculty of Arts turned out to be a remarkable phenomenon despite the difficult times and the short term of its existence. In the works dedicated to the study of the pedagogical and organizational activities of F.I. Shmit, A.I. Beletsky, S. A. Taranushenko, and other scientists, their contribution to the organization of the Free Faculty of Arts and their active participation in its life are emphasized.